Phenolic compounds: current industrial applications, limitations and future challenges - Albuquerque, Bianca R. (2018)
Phenolic compounds are natural bioactive molecules found mainly in plant tissues that have shown interesting bioactivities, such as antioxidant, antimicrobial, anti-inflammatory, and antiproliferative activities, among others, which has led to great interest in their use by several industries. However, despite the large number of scientific studies on this topic, some issues still need to be studied and solved, such as the understanding of the main actions of these compounds in organisms. Besides their large potential applicability in industry, phenolic compounds still face some issues making it necessary to develop strategies to improve bioavailability, sustainable technologies of extraction and refinement, and stability procedures to increase the range of applicability. This review focuses on the most recent advances in the applications of phenolic compounds in different technological and medicinal areas. In addition, techniques to improve their sustainable resourcing, stability and bioavailability will be presented and discussed. This journal is